Quantitative Assessment of H Reflex and F Response Values in Healthy and Paralyzed Limbs and Their Correlation with the Prognosis of CVA Patients - Heidari, Ali; Mortazavi, SeyedHasan; Omraninava, Melody; Hayati , Amirreza; Yousefi, Reza (Health Nexus, 2025)
Quantitative and objective evaluation of stroke patients with limb paralysis provides valuable insights into functional decline and treatment prognosis. The present study aims to quantitatively assess the H reflex and F response values in both healthy and paralyzed limbs and their relationship with the prognosis of recovery in paralyzed limbs of stroke patients. This descriptive-analytical study was conducted on 60 stroke patients hospitalized at Valiasr Hospital in Qaemshahr during 2022-2023. H reflex and F response values were measured using EMG-NCV for both healthy and paralyzed limbs at the onset of the disease, three months later, and six months later. The results were analyzed using the repeated measures test with SPSS software. The mean age of patients was 65.47 ± 8.57 years, with 58.3% (35 individuals) being male. The results revealed significant differences in Min F latency, Min M latency, and Min H latency in F response, as well as Max H amplitude in H reflex between healthy and paralyzed limbs (P0.05). H reflex and F response measurements offer valuable insights into patient recovery and the therapeutic management of stroke patients with paralyzed limbs.